2021
DOI: 10.3389/fphys.2021.770455
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Linking the Gut-Muscle Axis With Muscle Protein Metabolism and Anabolic Resistance: Implications for Older Adults at Risk of Sarcopenia

Abstract: Aging is associated with a decline in skeletal muscle mass and function—termed sarcopenia—as mediated, in part, by muscle anabolic resistance. This metabolic phenomenon describes the impaired response of muscle protein synthesis (MPS) to the provision of dietary amino acids and practice of resistance-based exercise. Recent observations highlight the gut-muscle axis as a physiological target for combatting anabolic resistance and reducing risk of sarcopenia. Experimental studies, primarily conducted in animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 168 publications
0
30
0
Order By: Relevance
“…These results indicate that catabolic conditions in CKD induce an imbalance between these two closely interacting pathways, leading to an accelerated rate of muscle wasting [ 26 , 27 ]. Recently, a growing body of evidence has focused on the involvement of microRNAs (miRNAs) [ 28 , 29 , 30 ] and gut microbiota [ 31 , 32 , 33 ] in muscle wasting. Alterations in miRNA expression in CKD can lead to abnormal protein metabolism and muscle regeneration through the modulatory effects of miRNAs on relevant intracellular signaling pathways [ 22 ].…”
Section: Mechanism Underlying Muscle Wasting In Ckdmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that catabolic conditions in CKD induce an imbalance between these two closely interacting pathways, leading to an accelerated rate of muscle wasting [ 26 , 27 ]. Recently, a growing body of evidence has focused on the involvement of microRNAs (miRNAs) [ 28 , 29 , 30 ] and gut microbiota [ 31 , 32 , 33 ] in muscle wasting. Alterations in miRNA expression in CKD can lead to abnormal protein metabolism and muscle regeneration through the modulatory effects of miRNAs on relevant intracellular signaling pathways [ 22 ].…”
Section: Mechanism Underlying Muscle Wasting In Ckdmentioning
confidence: 99%
“…Accumulating evidence has shown that gut microbiota dysbiosis can be associated with various diseases apart from localized gastrointestinal illnesses, including cardiovascular, metabolic, hepatic, respiratory, neurologic, and oncologic disorders [ 33 , 77 ]. Consequently, the concept of the gut-muscle axis has been proposed to describe the remote effects of gut microbiota-derived metabolites on muscle metabolism [ 31 , 32 , 33 ]. The causal relationship between gut dysbiosis and muscle wasting is mediated by the reduced bioavailability of dietary amino acids, chronic systemic inflammation, insulin resistance, mitochondrial dysfunction, and modulation of host gene expression [ 31 , 32 , 33 , 80 ].…”
Section: Mechanism Underlying Muscle Wasting In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it could be strongly suspected by the study of Fransen et al ( 17 ) who showed that microbiota transfer from elderly mice to axenic young mice stimulated immune pathways in the gut with bacterial components found in systemic circulation of the recipient mice capable to generate low-grade inflammation (NFκB pathway). Hence, we can speculate the existence of a gut-microbiota-muscle axis that could be also one of the determinant responsible for sarcopenia development during aging ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms underlying the relationship between gut microbes and muscle have not been fully defined, researchers have found that exercise training can alter the composition of the gut microbiota, possibly due to energy demand and use ( 13 ). Gut microbes may also stimulate insulin-like growth factor-1 (IGF-1) to increase skeletal muscle mitochondrial levels, promote skeletal muscle cell synthesis ( 14 ), or maintain or improve muscle mass by increasing glycogen storage using short-chain fatty acids (SCFA) ( 15 ). Many factors can cause changes in the gut microbiome, such as diet and exercise.…”
Section: Introductionmentioning
confidence: 99%